Purple Corn Extract as Anti-allodynic Treatment for Trigeminal Pain: Role of Microglia - Magni, Giulia; Marinelli, Alessandra; Riccio, Daniele; Lecca, Davide; Tonelli, Chiara; Abbracchio, Maria P.; Petroni, Katia; Ceruti, Stefania (Frontiers in Cellular Neuroscience, 2018)
Natural products have attracted interest in the search for new and effective analgesics and coadjuvant approaches to several types of pain. It is in fact well known that many of their active ingredients, such as anthocyanins and polyphenols, can exert potent anti-inflammatory actions. Nevertheless, their potential beneficial effects in orofacial painful syndromes have not been assessed yet. Here, we have evaluated the preventive effect of an anthocyanin-enriched purple corn extract against the development of orofacial allodynia, in comparison with isogenic yellow corn extract containing only polyphenols. Orofacial allodynia developed following induction of temporomandibular joint inflammation in male rats, due to the injection of Complete Freund’s Adjuvant, and was evaluated by von Frey filaments. Animals drank purple or yellow corn extracts or water starting from 11 days before induction of inflammation and up to the end of the experiment three days later. To highlight possible additive and/or synergic actions, some animals also received the anti-inflammatory drug acetyl salicylic acid. In parallel with the evaluation of allodynia, we have focused our attention on the activation of microglia cells in the central nervous system, as it is well-known that they significantly contribute to neuronal sensitization and pain. Our data demonstrate that purple corn extract is as effective as acetyl salicylic acid in preventing the development of orofacial allodynia, and only partial additive effect is observed when the two agents are co-administered. Yellow corn exerted no effect. Multiple mechanisms are possibly involved in the action of purple corn, including reduction of trigeminal macrophage infiltration and the shift of microglia cell polarization to an anti-inflammatory phenotype. In fact, in rats receiving yellow corn or water microglia cells show thick, short cell processes typical of activated cells. Conversely, thinner and longer microglia cell processes are observed in the brainstem of animals drinking purple corn extract; shape changes are accompanied by a reduction in the expression of pro-inflammatory molecules and increased production of anti-inflammatory mediators. Administration of purple corn extracts therefore represents a possible low-cost and easy way to reduce trigeminal-associated pain in various pathological conditions also thanks to the modulation of microglia reactivity.